Sentencing Disparity in Military Court Indecency Cases Surabaya: Ketidakadilan dalam Penetapan Hukuman pada Kasus Ketidaksenonohan di Pengadilan Militer Surabaya - Saiful Hariyanto; Rifqi Ridlo Phahlevy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Sentencing disparity is a persistent concern in criminal justice because unequal punishments for comparable offenses raise questions about fairness, proportionality, and legal certainty, including within military jurisdictions. Specific Background In the Indonesian military context, cases of indecency committed by members of the armed forces against the Extended TNI Family (KBT) fall under military court authority, where sanctions may include imprisonment and dismissal from service. Knowledge Gap Despite existing regulations and internal directives governing moral violations, limited research has systematically examined patterns of inconsistent sentencing and the judicial considerations underlying such differences in Military Court III Surabaya. Aims This study analyzes patterns of sentencing disparity and identifies factors shaping judicial reasoning in indecency cases involving TNI personnel against KBT within this jurisdiction. Results Normative legal analysis of four decisions shows variations in principal and additional punishments, including increases, reductions, consistency across appellate levels, and cases without dismissal due to prior discharge, reflecting differing emphases on retributive, corrective, and rehabilitative justice. Novelty The study provides a focused comparative examination of multiple case trajectories within a single military court region while assessing the application of internal TNI regulations and judicial discretion. Implications The findings indicate a need for clearer sentencing guidelines to ensure consistency, strengthen legal certainty, and maintain confidence in military justice processes. Highlights: Comparable misconduct received unequal prison terms and administrative sanctions across cases. Appellate review sometimes altered punishments while other cases remained unchanged through all levels. Judicial reasoning reflected different orientations toward punishment philosophies and case-specific conditions. Keywords:Sentencing Disparity; Military Court; Indecency Offense; TNI Personnel; Legal Consistency